Vagus Nerve Stimulation (VNS) in Super Refractory New Onset Refractory Status Epilepticus (NORSE) - Mohankumar Kurukumbi; James Leiphart; Anam Asif; Jing Wang (Case Reports in Neurological Medicine)
The treatment protocol of status epilepticus has many associated toxicities so there is interest in alternate nonmedicinal therapies for managing New Onset Refractory Status Epilepticus (NORSE) patients. Vagus nerve stimulation (VNS) is an FDA-approved therapy for refractory epilepsy that has been shown to decrease the frequency and severity of seizures. We present the case of a patient with new-onset refractory status epilepticus (NORSE) whose seizures were successfully treated with vagus nerve stimulation. A 25-year-old male with no history of epilepsy or other neurological disorders presented with altered mental status and generalized tonic-clonic seizures following a two-week history of an upper respiratory tract infection. Lumbar puncture showed neutrophilic pleocytosis, and he was treated for bacterial and viral meningoencephalitis. In spite of treatment, his seizures began increasing in frequency. On day three, the patient entered status epilepticus (SE) refractory to intensive pharmacotherapy with maximal doses of valproate, levetiracetam, and propofol. On day four, SE remained refractory, so pentobarbital was introduced with targeted burst suppression pattern on electroencephalography (EEG). Patient continued to be refractory to these measures, so a vagus nerve stimulator (VNS) was implanted (day eight). Following VNS implantation, EEG demonstrated significant reduction of seizure activity and subsequent magnet swiping continued aborting electrographic seizures. No SE or electrographic seizures were reported for seventy-two hours, but few occasional discharges were reported. Seizures eventually recurred on day fourteen and the patient succumbed to his multiple comorbidities on day seventeen. Due to the efficacy of VNS in refractory epilepsy, there was interest in using it in refractory status epilepticus. Multiple case reports have described a benefit from implantation of VNS in the treatment of SE. The successful use of VNS to acutely terminate status epilepticus for seventy-two hours in this critically ill patient adds to current evidence that there is utility in using VNS for refractory status epilepticus.